2010
DOI: 10.1007/s11325-010-0345-4
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between craniofacial morphology and sleep-disordered breathing in children in an undergraduate orthodontic clinic

Abstract: Even though few patients were suspected as having SDB, symptoms were related to many cephalometric variables and study model measurements. Since the etiology of SDB is believed to involve multiple factors, such patients may exhibit some risk of developing SDB in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Malformations of the maxilla, mandible, and associated structures can contribute to upper airway obstruction during sleep. Recently, studies using cephalometry and dental casts of patients with obstructive sleep apnea have shown an association with craniofacial morphological features such as a long and narrow face, transverse facial deficiency (high and narrow palatal arch), and retrognathia, in both adults (Hoekema et al , ; Johal and Conaghan, ; Riha et al , ; Nuckton et al , ; Okubo et al , ; Johal et al , ; Ishiguro et al , ; Lee et al , ; Gulati et al , ) and children (Marino et al , ; Pirila‐Parkkinen et al , , ; Tsuda et al , ; Ikavalko et al , ). In 6‐ to 8‐year‐old children, a recent study suggests that abnormal craniofacial morphology, more than excess body fat, increases the risk of obstructive sleep apnea (Ikavalko et al , ).…”
Section: Sleep Disorders Oral Health and Oral Functionmentioning
confidence: 99%
“…Malformations of the maxilla, mandible, and associated structures can contribute to upper airway obstruction during sleep. Recently, studies using cephalometry and dental casts of patients with obstructive sleep apnea have shown an association with craniofacial morphological features such as a long and narrow face, transverse facial deficiency (high and narrow palatal arch), and retrognathia, in both adults (Hoekema et al , ; Johal and Conaghan, ; Riha et al , ; Nuckton et al , ; Okubo et al , ; Johal et al , ; Ishiguro et al , ; Lee et al , ; Gulati et al , ) and children (Marino et al , ; Pirila‐Parkkinen et al , , ; Tsuda et al , ; Ikavalko et al , ). In 6‐ to 8‐year‐old children, a recent study suggests that abnormal craniofacial morphology, more than excess body fat, increases the risk of obstructive sleep apnea (Ikavalko et al , ).…”
Section: Sleep Disorders Oral Health and Oral Functionmentioning
confidence: 99%
“…Whereas in the current study, the presence of skeletal malocclusion, in the form of angle malocclusion (retrognathia/prognathia) and overjet, was significantly more common among school-age children with OSA compared with the preschool group. Craniofacial anatomical factors are believed to play a significant role in OSAS, together with upper airway compliance and muscle function mechanisms [26, 27]. D eng et al [28] found that a retrusive mandible and deficient chin are commonly detected in children aged 6–12 years presenting with OSA when compared with healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Along with the vast amount of research including animal experiments and literature reviews concerning airway and its influence on dentofacial growth and development, [9][10][11][12] many investigators have attempted to resolve pediatric OSAHS by the use of orthodontic appliances such as rapid maxillary expansion appliances. [13][14][15][16][17] However, few studies reported on the follow-up observation on the impact of OSAHS on patients treated with fixed orthodontic appliances.…”
Section: Introductionmentioning
confidence: 99%